REMOVAL OF IMPURITIES FROM MILLED AMORPHOUS SILICON DIOXIDE THROUGH THERMAL ANNEALING AND ACID LEACHING USING TAGUCHI METHODS FOR 3C SILICON CARBIDE PHOTOVOLTAIC APPLICATION - SUBRAMANIAN, VISALACHY (IRC, 2017)
In the past year, silicon carbide (SiC) technology have been advancing vastly in this competitive world. One of the problems encountered in producing a higher concentration of amorphous silicon dioxide for SiC for a photovoltaic application that it must undergo expensive purification process and several treatments to remove metal impurities dependent on the concentration of required silica. Considering the facts that SiC is one the most important element in the photovoltaic industry, this project aims to design an experiment with low cost and higher efficiency using Taguchi's Design of Experiment method for the purification process of amorphous silicon dioxide. There are 4 processing parameters with a total of nine experiments are conducted. The results of this experiment are analysed using the analysis of variance (ANOVA) technique by analysing the morphology changes of amorphous silicon dioxide by Scanning Electron Microscope (SEM) and X-Ray Fluorescence (XRF) which represents the element analysis and compared with the different purification stages to determine which has lower metal impurities concentration and yield high purity of silica. The optimum parameters for removal of impurities from amorphous silicon dioxide and yield high purity of silica are mechanical milling time of 120 minutes, drying temperature of 200oC, followed by thermal annealing temperature of 1000 oC and lastly acid leaching duration of 360 minutes. These results make this method very interesting for production of silica intended for photovoltaic application